Reviewing the devices of those subject to Sexual Harm Prevention Orders (SHPOs): iOS opportunities, limitations and strategies - Horsman, Graeme (Australian journal of forensic sciences, 2025)
In England and Wales, Management of Sexual or Violent Offenders (MOSOVO) teams are often tasked with managing offenders that are subject to Sexual Harm Prevention Orders SHPOs. These orders are put in place to protect the public and contain a series of prohibitions that allow for an offender's conduct to be regulated and reviewed. SHPOs can be used to govern how offenders use their digital devices, particularly with regard to accessing the internet and the sending of electronic communications. To ensure SHPO compliance, officers frequently conduct reviews of any offender's devices, sometimes manually by traversing a device's menus and screens. These device manual reviews are not easy to conduct, often done under time pressures and in the knowledge that any missed evidence of misconduct may facilitate an offender to continue any wrongdoing and potentially increase the risk of harm to members of the public. Further, it is not always technical specialists undertaking this role. This work outlines a manual review strategy for devices running the operating system iOS (Apple products) to support officers in this role. Guided by commonly included SHPO prohibitions, relevant digital traces for evaluating SHPO compliance are highlighted, and limitations surrounding determining user behaviour are also discussed.